The fortune at the bottom of the pyramid - Prahalad, C.K. (New Jersey: Pearson Education, Inc., 2006)
Contents: The market at the bottom of the pyramid,the power of dominant logic,the nature of the BOP market,the market development imperative,benefits to the private sector,BOP: a global opportunity,the ecosystem for wealth creation,reducing corruption: transaction governance capacity,developmente as social transformation,bussiness success stories from the bottom of the pyramid.
Include appendix
Keywords: Asistencia extranjera - Economía